Water Quality Assessment by Measuring and Using Landsat 7 ETM+ Images for the Current and Previous Trend Perspective: Lake Tana Ethiopia - Moges, M.A.; Schmitter, Petra S.; Tilahun, Seifu A.; Ayana, Essayas K.; Ketema, A.A.; Nigussie, T.E.; Steenhuis, Tammo S. (Scientific Research Publishing, Inc., 2017)
Recently there are signs of water quality impairment in Lake Tana, the largest fresh water in Ethiopia. The lake is the growth corridor of the government and supports millions of livelihood around. In order to sustain the benefit and maintain the ecosystem of the lake, the lake health has to be kept safe. Therefore monitoring and evaluation of the water quality of lake is very vital. This study focuses on current and previous trends water quality of the lake through measurements and Landsat Images near entry of Gumera River. Statistical analysis of the physical (Turbidity and STD and biological (Cha-a,) and chemical (DPC) water quality parameters were done. Linear and non-linear regression models between water quality parameter and reflectance of Landsat 7 ETM+ images were fitted based on band combinations. Pervious trend in turbidity was analyzed based on the regression models. The results showed that reflectance and turbidity satisfactorily result with an R2 ranging from 0.61 - 0.68. Form 1999-2014 the turbidity of the lake has indicated an increasing trend. Delta development near the entry of Gumera River has been enlarged by 48% because of an increase sediment inflow. The sign in the decreasing water quality of the lake was attributed to the non-point source sediment and nutrient inflow to the lake with high erosion rate from the watersheds. Measures to reduce the non-point source sediment and nutrient inflow by targeting the source areas (hot spots) in the agricultural watersheds need to be priority for stakeholders working on the soil and water conservation. Moreover, reducing the recession agriculture around the lake and wetland management could be crucial for improving lake water quality.